Parent–adolescent concordance on the Revised Diagnostic Interview for Borderlines (DIB‐R) and the Childhood Interview for Borderline Personality Disorder (CI‐BPD). (28th May 2017) - Wall, K.; Sharp, C.; Ahmed, Y.; Goodman, M.; Zanarini, M.C.
Abstract: While the degree of concordance between parent and adolescent self‐report of internalizing and externalizing pathology is well studied, virtually nothing is known about concordance in borderline pathology and the implication of parent–adolescent discrepancies for outcomes. The present study aimed to (1) examine discrepancies between parents and adolescents on two interview‐based measures of borderline personality disorder (BPD)—the Revised Diagnostic Interview for Borderlines (DIB‐R 22 ) and the Childhood Interview for Borderline Personality Disorder (CI‐BPD 23 ); and (2) investigate the implications of discrepancies for clinical outcomes. Diagnostic concordance on the DIB‐R and CI‐BPD showed rates of 82% and 94% respectively, with lower concordance demonstrated for dimensionally scored variables. Standardized difference scores between adolescent and parent reports on both borderline measures were significantly correlated with few interview‐based axis I diagnoses as reported by parents, but not adolescents themselves. Implications regarding the use of each measure for the assessment and diagnosis of borderline personality disorder are discussed. Copyright © 2017 John Wiley & Sons, Ltd.